Pengembangan Media Pembelajaran Video Animasi Doratoon untuk Meningkatkan Hasil Belajar IPAS Siswa Kelas V pada Materi Ekosistem yang Harmonis - Shinta Afifah Ramadhan; Novi Setyasto (Postgraduate, University of Mataram, 2025)
The purpose of this study was to determine the feasibility, effectiveness, and practicality of Doratoon animated video learning media to improve student learning outcomes. The type of research used is research and development using the Borg and Gall model. The population used in this study involved 23 fifth grade students of SDN Wedarijaksa 03. Data collection techniques used test techniques (pretest - posttest) and non-tests in the form of interviews, questionnaires, observations, score lists, and documentation. The feasibility of the media is shown from the results of material and media expert validation which shows that the media is declared very feasible with an average score of 95%. The practicality of the learning media is shown from the results of teacher and student response questionnaires to the use of the media showing a “very positive” level of satisfaction, with an average score of 100% from teachers and 98.17% from students. The effectiveness of the learning media is evidenced by the small group N-Gain value of 0.67 and the large group of 0.69 classified in the “medium” category. The results showed that Doratoon animated learning media met the criteria of feasible, practical, and effective to improve students' social studies learning outcomes.